PENERAPAN INOVASI ALAT PENGIPAS BERAS BERBASIS LISTRIK UNTUK MENINGKATKAN EFISIENSI PASCAPANEN PETANI DI NAGARI CUPAK KABUPATEN SOLOK - Susanti, Oknovia; Afriansyah, Rizki; Rozali, Fuadil Fajri; Yulinda, Yulinda; Yanda, Hendri; Yuhelmis, Yuhelmis (LPPM Universitas Andalas, 2025)
This activity was carried out in Nagari Cupak, Solok Regency, where local farmers still use traditional tools and manual labor to clean the husks from rice. This manual process not only takes a long time but is also inefficient in separating high-quality rice grains from empty ones. Rice is the primary agricultural product and staple food of the Indonesian people, so the quality of the rice harvest significantly impacts farmers' well-being and food security. However, rice harvests are often unsatisfactory due to the presence of empty grains that must be manually separated by farmers. Therefore, the community service team provided a solution in the form of an electric rice separator to improve work efficiency and harvest quality. This rice separator is designed to automatically separate filled and high-quality grains from empty or imperfect grains. This activity aims to design and implement a rice separator machine that can help farmers in Nagari Cupak optimize their harvest yields. The methods used include field surveys, design, training, and monitoring and evaluation. The field survey involved the team conducting direct observations of farmers regarding the actual conditions they face, designing the machine according to farmers' needs, and then conducting training for farmers on how to use the rice separator machine and monitoring the machine. The results of the tool testing showed that it could separate rice at a capacity of up to 10 kg per minute, a significant increase compared to the manual method, which could only process around 6 kg per minute.